STATE AND PROSPECTS OF CONSUMER MARKET DEVELOPMENT IN UKRAINE IN THE CONTEXT OF FOREIGN EXPERIENCE - Харабара, Віолетта; Грешко, Роман Ігорович; Третякова, Олена Василівна (Modern engineering and innovative technologies, 2020)
In the article the question of becoming and problem of development ofthe mortgage crediting of Ukraine is considered, the dynamics of mortgagemarket of modern Ukraine was probed in the conditions of world mortgagecrisis. Is analysed condition of modern mortgage market of the USA andinfluence of crisis processes in the USA and Europe on condition ofmortgage market of Ukraine.
Keywords: mortgage market; mortgage crisis; mortgage crediting; mortgage; credit; bank